Slipping the reins on the Trojan horse: Interpreting self-directed learning as a political concept - Stephen Brookfield (Adult Education Research Conference, 1993)
This paper argues that self-direction can be interpreted as part of a distinctively American cultural tradition that emphasises the individual's standing against repressive interests. As such, the concept has some powerful political underpinnings which, if made explicit, could play a substantial role in a critical practice of adult education . In this paper I want to argue that critical adult educators may be making a strategically premature decision to dismiss self-directed learning and practice as wholly accommodative. We could miss an important tactical opening in the fight for a critical practice of adult education if we conclude too decisively that self-directed learning as an idea has been so hopelessly compromised that it can only function as an agent of domestication. If interpreted politically, self-directed learning could play an important role (along with critical theory, critical pedagogy and other work on transformative and emancipatory education) in providing a rationale for a critical practice of adult education. The case for self-direction as an inherently political concept rests on two arguments. First, that at the intellectual heart of self-direction is the issue of control, particularly control over what are conceived as acceptable and appropriate learning activities and processes. Second, that exercising self-direction requires that certain conditions be in place, conditions that are essentially political in nature.